Faith, culture and youth ministry in South Africa: The impact of traditional cultural practices on the faith formation of youth - Weber, Shantelle (Missionalia, 2021)
Postmodern youth are deeply spiritual. These youth sometimes do not even call themselves religious, yet at the root of their postmodern pluralism and relativism, they do have a deep hunger for God. It is for this reason that congregations need to do all possible to engage these youth, assisting them in their quest for faith and growth in that faith, but this has to be done in a responsible and effective way. This paper will explore the relationship that culture has in the faith formation of the youth. In this sense, it reflects on the church’s mission to young people as they wrestle with the tensions they may experience between faith and culture. Due to the diversity of culture and faith in South Africa, our attention is focussed on examples of traditional practices which involve youth from various African cultures. Theological reflection on the religious aspects of culture and society as well as the spiritual dimension of individual life is prioritized.